ЦИФРОВА СИСТЕМА КЕРУВАННЯ РЕЗОНАНСНОГО ІНВЕРТОРА НАПРУГИ З САМОЗБУДЖЕННЯМ - Гуцалюк, В.Я.; Зубков, І.С. (Інститут електродинаміки НАН України, Київ, 2024)
Phase-locked loop systems (PLL) are widely used in control circuits of transistor resonant voltage inverters of induction heating installations. One of disadvantages of PLL systems is low speed, which is caused by the presence of a low-pass filter. This disadvantage is absent in self-oscillating systems, when the switching moment of the transistors is determined on each of half periods. At the same time, an asymmetry of half periods is possible, which is a significant disadvantage if there is a transformer at the output of the inverter. A self-oscillating digital control system for a resonant voltage inverter and equal half periods durations of the inverter output voltage has been developed. It can work with different methods of regulating the output current and allows to provide switching modes of transistors with minimal power losses. References 7, figures 5.